Theoretical Study of Electronic Properties and Vibration Frequencies for Tri-Rings Layer (6, 0) Linear (Zigzag) SWCNT - Kubba, Rehab; Samawi, Khalida (Iraqi Journal of Science, 2023)
DFT (3-21G, 6-31G and 6-311G/ B3LYP) and Semi-empirical PM3 methods were applied for calculating the vibration frequencies and absorption intensities for normal coordinates (3N-6) of the Tri-rings layer (6,0) Zigzag single wall carbon nanotube (SWCNT) at their equilibrium geometries which was found to have D6h symmetry point group with C-C bond alternation in all tube rings.as well as mono ring layer. Assignments of the modes of vibration were done depending on the pictures of their modes applying by Gaussian 03 program. The whole relations for the vibration modes were also done including (CH stretching, CC stretching, deformation in plane of the molecule (δCH, δring and δCCC), deformation out of plane of the molecule (CH and ring (CCC). Also include the assignment of puckering, breathing and clock-anticlockwise bending vibrations.Comparison for the geometry (the relations for axial bonds, which are the vertical C-C bonds (linear bonds) in the rings layer and for circumferential bonds which are the outer ring bonds), electronic properties and IR active vibration frequencies (asymmetric modes) of (Mono and Tri) rings layer were done. Clear relationships were found in the results of an odd layer number (Mono and Tri-rings layer). The theoretical results allow a comparative view of the charge density at the carbon atoms too.